Exploring the use of regular reflections in student collaboration: a case study in higher education - Schürmann, Verena; Bodemer, Daniel; Marquardt, Nicki (Frontiers in Education, 2025)
IntroductionWith the growing emphasis in higher education on fostering collaboration and reflection, this study examines the intersection of these two concepts by exploring the use of regular reflections in student collaboration.MethodsAn embedded case study approach was employed, investigating four student teams over a 15-week interdisciplinary project course at a higher education institution. Each team participated in four joint reflections, supported by Behaviorally Anchored Rating Scales (BARS). Multiple data sources, including questionnaires, interviews, and documents, were collected at both the team and individual levels.ResultsThe findings reveal a positive improvement in students’ self-assessed collaboration in three out of the four teams over the semester. These teams also experienced an increase in psychological safety. Triangulation and the comparison of two contrasting cases provided deeper insights into these patterns. While the data indicated general satisfaction with the reflection sessions and the BARS, several challenges, influencing factors, and areas for improvement were identified.DiscussionThis study offers valuable insights into the dynamics and quality of joint reflections within student teams. It provides practical recommendations for integrating reflective practices into higher education courses and highlights avenues for future research.